2011
DOI: 10.1007/s11104-011-0720-3
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of nitrogen transformation processes to total N2O emissions from soils used for intensive vegetable cultivation

Abstract: The rapid expansion of intensively farmed vegetable fields has substantially contributed to the total N 2 O emissions from croplands in China. However, to date, the mechanisms underlying this phenomenon have not been completely understood. To quantify the contributions of autotrophic nitrification, heterotrophic nitrification, and denitrification to N 2 O production from the intensive vegetable fields and to identify the affecting factors, a 15 N tracing experiment was conducted using five soil samples collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(39 citation statements)
references
References 52 publications
2
35
2
Order By: Relevance
“…The major N 2 O source is denitrification (Skiba et al 1997;Skiba, Smith 2000;Ruser et al 2001). High rate of N fertiliser application increases concern regarding N 2 O emissions from intensively farmed fields (He et al 2009;Pang et al 2009;Lin et al 2010;Zhu et al 2011). Although N 2 O emissions from the soil increase with the amount of N fertiliser (Eichner 1990;Bouwman 1996;Verma et al 2006;Jones et al 2007;He et al 2009;Pang et al 2009;Lin et al 2010;Mapanda et al 2011), there is still a lack of data for fertiliserintensive systems (Pfab et al 2012).…”
mentioning
confidence: 99%
“…The major N 2 O source is denitrification (Skiba et al 1997;Skiba, Smith 2000;Ruser et al 2001). High rate of N fertiliser application increases concern regarding N 2 O emissions from intensively farmed fields (He et al 2009;Pang et al 2009;Lin et al 2010;Zhu et al 2011). Although N 2 O emissions from the soil increase with the amount of N fertiliser (Eichner 1990;Bouwman 1996;Verma et al 2006;Jones et al 2007;He et al 2009;Pang et al 2009;Lin et al 2010;Mapanda et al 2011), there is still a lack of data for fertiliserintensive systems (Pfab et al 2012).…”
mentioning
confidence: 99%
“…If there was no leaching or loss via runofs, all available N will be adsorbed by plant roots and used for growth. However, nitriication and denitriication processes (both produce greenhouse gas N 2 O) also occurred between ammonium and nitrate N, causing new balance among diferent N components [2,4,7].…”
Section: Overview Of Soil N Transformationsmentioning
confidence: 99%
“…In addition to N input by anthropogenic activities, N output via crops harvest or human-induced runofs with irrigation could occur simultaneously in agricultural soils (Figure 1). Moreover, the complicated N transformations going on in soil ecosystems also account for large part of N output from soils [7]. For example, N mineralization associated with transforming organic N into inorganic N might induce more N leaching with runofs or underground water; nitriication process could increase N loss from soils via gas emissions [2,7,8] ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also concluded that application of high dose of nitrogen fertiliser resulted in the increase of concerns regarding to the N 2 O emissions from intensively farmed fields (Zhu et al, 2011;He et al, 2009;Pang et al, 2009;Lin et al, 2010;Šima, 2014). Although intensive research conducted by various researchers (e.g.…”
Section: Introductionmentioning
confidence: 99%